Pengaruh Dimensi terhadap Volume Gas HHO dan Daya Listrik pada Proses Elektrolisis - Pradigdo, Dedy; Soeparman, Sudjito; Widodo, Agung Sugeng (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2018)
The electrode area have an effect on HHO gas production volume, this phenomena influenced by electric power absorbed from the energy source to the electrode. It is necessary to examine how much the influences on process of the water electrolysis. In this research the effect of the electrode total area on the electrolysis process analyzed to determine the volume of HHO gas and electric power absorbed. The experimental method by testing the extent of several electrodes without the connection and calculating the entire surface on the electrode. The electric power is absorbed among other L1 = 6.413 mm2 : 5,2 ml : 0,774 watt, L2 = 10.028 : 28 mm2 : 7 ml : 0,9030 watt, L3 = 14.328 mm2 : 15 ml : 2,451 watt and L4 = 14.3608 mm2 : 20 ml : 6,192 watt. In this research, the highest result on the electrode having L4: 14.360,8 mm2 = 6,192-watt area. This result influenced by the surface area reacting with water at the anode and cathode of the 12 Volt 70 AH battery and the capacity of the electrolysis generator.